2022
DOI: 10.1021/acsphyschemau.2c00032
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Dynamical, and Entropic Differences between SARS-CoV and SARS-CoV-2 s2m Elements Using Molecular Dynamics Simulations

Abstract: The functional role of the highly conserved stem-loop II motif (s2m) in SARS-CoV and SARS-CoV-2 in the viral lifecycle remains enigmatic and an intense area of research. Structure and dynamics of the s2m are key to establishing a structure–function connection, yet a full set of atomistic resolution coordinates is not available for SARS-CoV-2 s2m. Our work constructs three-dimensional coordinates consistent with NMR solution phase data for SARS-CoV-2 s2m and provides a comparative analysis with its counterpart … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 103 publications
0
22
0
Order By: Relevance
“…Similarly, it is interesting to note that, despite having the same size, the monomer bands for the reference s2m and s2m G15U migrate differently in the TBM gel (Figure 5, right, arrow 1 and 1’), suggesting that they have different monomer conformations in the presence of MgCl 2 . Our MD simulations for the reference s2m revealed that it has a kinked 3D structure; however, it is possible that the additional U15-A29 base pair in the upper stem of s2m G15U results in a more linear structure that will migrate further through the TBM gel and MD simulations are in progress in our laboratories to test this hypothesis (Kensinger et al 2022). Thus, we cannot determine if the single dimer band observed for the s2m G15U in the TBM gel (Figure 5, right, arrow 3) is originating from a mixture of linear kissing dimer and duplex conformations which will migrate at the same position, or from the duplex conformation formed spontaneously from an unstable kissing dimer during incubation and migration through the gel (Shetty et al 2010).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, it is interesting to note that, despite having the same size, the monomer bands for the reference s2m and s2m G15U migrate differently in the TBM gel (Figure 5, right, arrow 1 and 1’), suggesting that they have different monomer conformations in the presence of MgCl 2 . Our MD simulations for the reference s2m revealed that it has a kinked 3D structure; however, it is possible that the additional U15-A29 base pair in the upper stem of s2m G15U results in a more linear structure that will migrate further through the TBM gel and MD simulations are in progress in our laboratories to test this hypothesis (Kensinger et al 2022). Thus, we cannot determine if the single dimer band observed for the s2m G15U in the TBM gel (Figure 5, right, arrow 3) is originating from a mixture of linear kissing dimer and duplex conformations which will migrate at the same position, or from the duplex conformation formed spontaneously from an unstable kissing dimer during incubation and migration through the gel (Shetty et al 2010).…”
Section: Resultsmentioning
confidence: 95%
“…Notably, only a two-nucleotide difference exists between the s2m of SARS-CoV-2 and SARS-CoV, the related virus responsible for the 2002-2003 outbreak of “SARS.” One of those mutations, G>U at position 31 (G31U) of the s2m (29,758 in the reference SARS-CoV-2 genome, EPI_ISL_402123), has previously been conserved as a G in all other reported s2m elements, and our earlier study revealed that G31U is the causative mutation between differences in dimerization properties in SARS-CoV-2 s2m and SARS-CoV s2m, as well as in miR-1307-3p binding (Imperatore et al 2022; Zhao et al 2020). Moreover, our molecular dynamics (MD) simulation study showed that these dimerization differences are likely caused by increases in structural flexibility of the terminal loop in SARS-CoV-2 s2m compared to the rigid GNRA-like pentaloop motif found in the SARS-CoV s2m (Kensinger et al 2022). In SARS-CoV-2 s2m, an expansion to a “nonaloop” was computed to confer an entropic penalty, potentially explaining the reduction in kissing complex formation, the intermediate step in duplex formation (Kensinger et al 2022).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is facilitated by finding the eigenvectors of the covariance matrix of atomic coordinates C , where each respective eigenvalue is a proportion of the total position variance. Ultimately, this procedure enables classification of simulated structures into conformational substates (CS), organized by structural similarity and dissimilarity. , Application of the k -means clustering algorithm partitioned PCA-reduced MD data into CSs that maximize dissimilarity between substates and identify representative centroid structures. , We performed PCA on different selections of atoms, particularly, the entire s2m (nt. 1–41) and the terminal loop (nt.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported differences in the atomistic structures and dynamics of the s2m of ancestral SARS-CoV and SARS-CoV-2 . Despite only two mutations (U5C and G31U) distinguishing SARS-CoV-2 s2m from SARS-CoV s2m, experimental and computational evidence show that the secondary and tertiary structures change drastically due to a base pair register shift. ,,, Aside from U5C and G31U, it has been reported that SARS-CoV-2 s2m has obtained other mutations, including a G15U (G29742U) substitution, which was first reported in May 2020, and most recently in April 2022 within the “Deltamicron” recombinant lineage. , In this case, Delta 21J_AY.4 and Omicron 21K/BA.1 variant genomes recombined resulting in a hybrid displaying signature mutations from both Delta and Omicron, with G15U being characteristic of the parent Delta variant. , …”
Section: Introductionmentioning
confidence: 99%